Molecular Epidemiology of Enterovirus A71 in Surveillance of Acute Flaccid Paralysis Cases in Senegal, 2013–2020 - Ndack Ndiaye; Fatou Diène Thiaw; Amary Fall; Ousmane Kébé; Khadija Leila Diatta; Ndongo Dia; Malick Fall; Amadou Alpha Sall; Martin Faye; Ousmane Faye (Vaccines, 2022)
Enterovirus A71 (EV-A71) is a non-polio enterovirus that currently represents a major public health concern worldwide. In Africa, only sporadic cases have been reported. Acute flaccid paralysis and environmental surveillance programs have been widely used as strategies for documenting the circulation of polio and non-polio enteroviruses. To date, little is known about the molecular epidemiology of enterovirus A71 in Africa where resources and diagnostic capacities are limited. To fill this gap in Senegal, a total of 521 non-polio enterovirus isolates collected from both acute flaccid paralysis (AFP) and environmental surveillance (ES) programs between 2013 and 2020 were screened for enterovirus A71 using real-time RT-PCR. Positive isolates were sequenced, and genomic data were analyzed using phylogeny. An overall rate of 1.72% (9/521) of the analyzed isolates tested positive for enterovirus A71. All positive isolates originated from the acute flaccid paralysis cases, and 44.4% (4/9) of them were isolated in 2016. The nine newly characterized sequences obtained in our study included eight complete polyprotein sequences and one partial sequence of the VP1 gene, all belonging to the C genogroup. Seven out of the eight complete polyprotein sequences belonged to the C2 subgenotype, while one of them grouped with previous sequences from the C1 subgenotype. The partial VP1 sequence belonged to the C1 subgenotype. Our data provide not only new insights into the recent molecular epidemiology of enterovirus A71 in Senegal but also point to the crucial need to set up specific surveillance programs targeting non-polio enteroviruses at country or regional levels in Africa for rapid identification emerging or re-emerging enteroviruses and better characterization of public health concerns causing acute flaccid paralysis in children such as enterovirus A71. To estimate the real distribution of EV-A71 in Africa, more sero-epidemiological studies should be promoted, particularly in countries where the virus has already been reported.